The assessment of functionality of the Diagnosis-Related Group (DGR) system by its users - Włach, Rafał; Książek, Piotr; Drop, Bartłomiej; Tkaczuk-Włach, Joanna (Polish Journal of Public Health, 2013)
Introduction. The authors of the system based on the grouping of the cases, depending on the type of diagnosis and procedures performed were Robert Barclay Fetter and John Devereaux Thompson of Yale University. For the first time DRG was implemented in New Jersey at the beginning of 1980 and in 1987. The decision of the authorities of New York DRG became the basis for the settlement. of the patients. In Europe, the model based on the DRG billing applies in almost all EU countries except the Czech Republic and Slovenia. In Poland, the scheme was introduced in July 2008, which caused numerous controversies due to changes in the financing of health services.Aim. The aim of the survey was to assess the functionality of a web-based DRG grouper.Material and methods. The survey was performed in February 2009 in 200 hospitals. The participation in the survey was optional and only 14% of users decided to fulfill the questionnaire. The collected data was analyzed and presented in tables. The surveyees were divided into the following professional groups: doctor, medical secretaries in the wards, employees of medical statistics epartment/department of settlements with the NHF, other groups.Conclusions. The results show that the most useful functionality is that of grouping, whereas the least useful is that of a duration of hospitalization. You can find a very similar distribution of functional suitability grouper in all 4 treatment groups. The users mainly use the software to determine the correct DRG groups, and much less likely to make coding optimization.